Representation of Communicative and Pragmatic Frame ‘Intellect’ In English, German and Russian Paremiological World Pictures - Shaimardanova, Milyausha R (2021)
The purpose of the study is to conduct a cognitively-comparative analysis of the representation of the communicative-pragmatic frame intellect (Russianум, German Klugheit) objectified in proverbs of English and Russian languages, which, being a reflection of the world view of a particular ethnic group, are a conventional way of expressing stereotypes of the people.The scientific novelty of the study lies in a comprehensive analysis of stereotypical assessments of the intellectual abilities of an individual as a representative of a particular society, through the study of paremias containing the nomination of the intellect – foolishness binome in the English, German and Russian paremiological view of the world.The article bears the result of the study of 1243 proverbial units – 412 English, 433 German and 398 Russian proverbs and sayings. As a result, universal and unique stereotypical representations of the value and the availability of knowledge and intelligence were revealed; the relationship between the level of mental abilities and behavior, luck; dependence of intelligence on alcohol, age, wealth and happiness.In addition, a correlation was determined between related (English and German) and unrelated (Russian) languages, which, in turn, facilitates the process of cognitive learning of the languages studied. Consequently, the article contributes to solving the problems of intercultural communication.